Applying In Dubio Pro Natura in Environmental Crime Cases: Legal Perspectives in Indonesia - Ramli, Asmarani; Putra, Tegar Islami; Dewanti, Natasya Fitri; Kinasih, Salisa Widyaning; Arifin, Ridwan; Idris, Siti Hafsyah (Faculty of Law Universitas Negeri Semarang, 2023)
This research aims to analyze the application of the